Corporate governance, diversification and performance of manufacturing and construction firms in Singapore : a multi-year study - Chia, Shini (2008)
This research paper examined the relationship between the extent of diversification (product and geography) and corporate governance (CG). To gain a further understanding of this relationship, we also examined how independent variables of diversification and CG affect a firm’s performance, which was measured by Tobin’s Q. This research is based on data collected from 220 manufacturing and construction companies listed on the Singapore Stock Exchange (SGX) from years 2000 to 2004.